Формирование полированной поверхности халькогенидов Bi и Sb в травильных композициях K2Cr2O7–HBr - Pavlovich, I. I.; Tomashik, Z. F.; Tomashik, V. N.; Stratiichuk, I. B. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The polishing etchants were developed and recommendations were given as to their use for processing of semiconductor materials which are used for the manufacture of work items of thermoelectric devices.